EDUKASI PEMILAHAN SAMPAH ORGANIK DAN ANORGANIK DI LINGKUNGAN SEKOLAH MENENGAH ATAS - I Gusti Ayu Ketut Meliyani; Ida Ayu Oka Martini (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
The Community Service Program (KKN) of Universitas Pendidikan Nasional (Undiknas) with the theme Eco Smart Community was conducted in Pemecutan Klod Village, West Denpasar District, as a form of students’ contribution to sustainable development. The main problem faced by the village is the lack of effective waste management, particularly in the separation between organic and inorganic waste. To address this issue, KKN students implemented the activity “Education on Organic and Inorganic Waste Sorting in High School Environments” at SMAN 12 Denpasar. The aim was to improve students’ awareness, knowledge, and behavior in waste management through education and direct practice. The methods used included socialization, sorting practice, and the creation of creative products such as organic and inorganic waste bins. The results showed an increased awareness among students about waste separation and a cleaner school environment. This program supports the Denpasar Clean and Green policy and encourages youth involvement in environmentally conscious community development. Keywords: Education, Waste Sorting, Organic, Inorganic, School